2016
DOI: 10.15376/biores.11.2.4252-4267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Suspended Matter on the Physico-Chemical Properties of Black Liquor from Alkali-Oxygen Pulping of Rice Straw

Abstract: Black liquor (BL) can be regarded as the energy and alkali resource of the pulping mill. In this work, the effects of the characteristics of black liquor derived from the alkali-oxygen pulping of rice straw were studied. Through analyses of the chemical and physical properties, especially the thermodynamics properties, which depend on suspended matter and alkalinity, it was shown that the removal of the suspended matter from the black liquor could effectively improve its thermodynamic properties, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Thermal degradation of polymers is a complex process that produces a wide range of low-molecular-weight (LMW) compounds. Although the MS analysis of the volatile products evolved during TG measurements offered detailed information on the thermal behavior of the BL, drawbacks still exist, such as one m / z signal from MS analysis possibly corresponding to various fragmentation ions like the m / z 18 representing H 2 O + and NH 4 + and m / z 44 for CO 2 + and C 2 H 4 OH + . However, temperature evolution during TG analysis might differ from some compounds, and FTIR also offers its characteristic functional group.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal degradation of polymers is a complex process that produces a wide range of low-molecular-weight (LMW) compounds. Although the MS analysis of the volatile products evolved during TG measurements offered detailed information on the thermal behavior of the BL, drawbacks still exist, such as one m / z signal from MS analysis possibly corresponding to various fragmentation ions like the m / z 18 representing H 2 O + and NH 4 + and m / z 44 for CO 2 + and C 2 H 4 OH + . However, temperature evolution during TG analysis might differ from some compounds, and FTIR also offers its characteristic functional group.…”
Section: Results and Discussionmentioning
confidence: 99%
“…in the BL with its pyrolysis quantitatively. Both our previous research 22 and and that of Cardoso 23 have examined the effect of silicon on the physicochemical properties of BL, which reflected that silicon hampered the pyrolysis process. Zhang 24 found that silica particles and lignin molecules are connected to form hydrogen bonds through silanol groups (Si−O−H), which limited the combustion of BL seriously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under an alkali and oxygen pressure environment, non-phenol structures in lignin are easily depolymerized and broken into low molecular weight products [ 10 ], which leads to the fibers swelling with more charge and superior ductility. Additionally, silica in black liquor can be deposited on the fiber surface, improving the brightness and strength of pulp, which solves the problem of silicon interference in the alkali recovery process [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis products and yield depends on the lignin origin, , pulping conditions, and their isolation process. , BL contains lignin residue, hemicellulose, and some other chemicals including Na 2 CO 3 , Na 2 SO 4 , NaOH, and Na 2 S, because they are used in the pulping processes. , These impurities in lignin or BL solid can influence the pyrolysis process ,, and the product distribution because these impurities may lead to secondary reaction (such as vapor cracking) during the pyrolysis, consequently, decreasing the bio-oil yield . Yildiz et al reported that an ash content of up to ca.…”
Section: Introductionmentioning
confidence: 99%